Construction and Project Management - krishnamurthy ([S.l.] : CBS Publishers & Distributors, 2008)
The book aims to meet the growing needs of construction management and project management education in the Indian context. Topics of discussion include objectives and concerns of construction management management of resources project management network techniques contract management selection of contractors tenders and conditions of contract legal aspects of contract execution of works and site, organisation machinery used in construction in general quality control safety management cost effectiveness and increasing role of computers in all spheres of design, construction and management. Chapter on project management provides general management practices as applied to construction management projects, enlarging the focus of application of management techniques. The additional information relating to proforma for site inspection of works, list of BIS relating to construction guidelines and safety codes freshly introduced would be of immense value to any construction management consultant. This book will serve as a text to students, a companion to young professionals, a source of information to practitioners, and a reference guide for project planning to all those engaged in construction industry. 1 construction management. 2 contract management. 3 management of resources. 4 project management. 5 network analysis. 6 selection of contractor. 7 tenders and conditions of contract. 8 legal aspects of contracts. 9 machinery for building works. 10 execution and site management of works. 11 quality control management. 12 safety management. 13 cost effectiveness. 14 computerisation.
Keywords: Project management; Construction industry; Management